Shoulder muscle endurance: the development of a standardized and reliable protocol - Roy, J. S.; Ma, B.; MacDermid, J. C.; Woodhouse, L. J. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2011)
Background Shoulder muscle fatigue has been proposed as a possible link to explain the association between repetitive arm use and the development of rotator cuff disorders. To our knowledge, no standardized clinical endurance protocol has been developed to evaluate the effects of muscle fatigue on shoulder function. Such a test could improve clinical examination of individuals with shoulder disorders. Therefore, the purpose of this study was to establish a reliable protocol for objective assessment of shoulder muscle endurance.